Effect of Abengourou forastero cocoa against doxorubicin-induced cardiotoxicity in experimental rats - Amidou Dembele; Abou Joël Landry Okon; Bernard Nazaire Djyh; Philippe Sansan Kambou; Joseph Allico Djaman; Mireille Tre-Yavo; Jean David N’guessan (International Journal of Phytomedicine, 2020)
Oxidative stress is a determining factor in the pathophysiology of heart disease. This study aimed at evaluating the protective activity of Abengourou Forastero cocoa in doxorubicin-induced cardiotoxicity in rats. Thirty (30) wistar rats divided into 5 groups were orally pretreated with distilled water, resveratrol (25 mg/kg/day) or defatted Abengourou Forastero cocoa powder (1000 and 1500 mg/kg/day) for sixty (60) consecutive days. A single dose of doxorubicin (15 mg/kg/day) was administered on day 59 by intraperitoneal route. The biochemical parameters were assessed and a histological examination of the heart was performed. This study showed that doxorubicin treated animals exhibited a significant increase of alanine aminotransferase, aspartate aminotransferase, lactate dehydrogenase, phosphocreatine kinases, creatine kinases, total cholesterol, triglycerides, and LDL-cholesterol levels in serum. However, a decrease of HDL-cholesterol and an alteration of cardiac tissue were noticed. Preventive treatment with Abengourou Forastero cocoa at doses of 1000 and 1500 mg/kg significantly reduced the biochemical and histological alterations induced by doxorubicin. Results showed that Abengourou Forastero cocoa protects and prevents against doxorubicin-induced cardiac damage.